Comparison of the Effectiveness of Wound Care Methods on Post Operative Wound Healing Time and Length of Stay in Cancer Patients - Silvia Handayani; Fatmawati Fatmawati; Ifriani Ifriani; Nia Rahmanandha Putri; Devia Ola Yulia (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cancer patients undergoing surgery have a high risk of delayed wound healing, which can result in increased length of stay (LOS) and increased costs and the risk of complications.. through modern wound care can accelerate post-operative wound healing and shorten patient LOS. This study aims to determine the effectiveness of wound care methods on post-operative wound healing time and LOS in cancer patients. The study used a quasi-experimental design with a non-equivalent control group design with a post-test only. The sample usedrandom block samplingat Dr. M. Djamil Padang General Hospital using 60 respondents. The research design was pre-experimental with two group posttest. The sampling technique used block random and obtained 60 cancer patients at Dr. M. Djamil Padang General Hospital. Data were collected after obtaining ethical approval and hospital permission from postoperative cancer patients treated in the operating room of Dr. M. Djamil Padang General Hospital. Data collection was carried out through observation of wound care methods and assessment of wound healing time using standardized observation sheets, as well as searching electronic medical records to obtain length of stay (LOS) data. Wound healing time was calculated from the first day of treatment until the wound was declared healed. analysis was carried out using statistical testsMann Withnay (Non normal distribution). Results study show thatThere is an influence of modern wound care on post-operative wound healing time and LOS in cancer patients in the surgical ward of Dr M Djamil Padang General Hospital in 2025.